GE_GERICHTE P/21151/2019 vom 2. November 2020 - GE Cour de justice (2020)
DEMANDE ADRESSÉE À L'AUTORITÉ;RÉVISION(DÉCISION);FALSIFICATION(ACTIVITÉ);PLAQUE DE CONTRÔLE | LCR.97.al1.lete; LCR.97.al1.letf; OCR.96; CPP.410.al1.leta